Pharmacokinetic In Vivo Comparison Using 1-Stage and Chromogenic Substrate Assays with Two Formulations of Hemofil-M - Lee, Christine; Barrowcliffe, Trevor; Bray, Gordon; Gomperts, Ed; Hubbard, Anthony; Kemball-Cook, Geoffrey; Lilley, Patricia; Owens, Dale; Von Tilberg, Louis; Pasi, John (Thrombosis and Haemostasis, 1996)
In a study to demonstrate the safety and pharmacokinetics (half-life and recovery) of two different method M purified AHF (Hemofil-M) concentrates processed in the USA and Spain, two different methods of factor VIII assay (one-stage clotting and chromogenic) have been compared in vivo. The study was a single centre blinded, randomised, crossover study. Twelve patients with severe haemophilia A (VIII: C <2 u/dl) were divided into two subgroups of six. None had received factor VIII concentrate within 48 h preceding the study. Twenty-four pharmacokinetic studies were performed in the 12 patients. Each subgroup received two different lots of study material (US and Spanish) at a dose of 50 u/kg seven days apart. A second randomisation was nominal potency, high: 1000 u or mid: 500 u per vial. The potency label was a one-stage clotting assay using the mega I standard. A standard pharmacokinetic study was performed over 24 h and each blinded sample was analysed in duplicate by a one-stage clotting (aPTT) and a chromogenic (Chromogenix AB; CS) assay at the Royal Free and NIBSC. Pharmacokinetic modelling was performed. The mean label for Hemofil-M using the chromogenic substrate assay was 79% that using the one stage assay (Mega I standard). The recovery was 17-28% higher measured by chromogenic compared to the clotting assay. Since most clinicians use the clotting assay, potency labelling using the chromogenic assay, will overestimate predicted Hemofil-M recovery by as much as 25%.